A dignidade da pessoa humana e a efetividade do direito social à saúde sob a óptica jurisprudencial - Picado, Fernanda de Siqueira (2010)
This study was aimed to analyse the principle of the human being' s dignity and the effectiveness of the right to health, including the current debate regarding the Judiciary Role to implement them. The content of the human dignity principle enables to identify the relation between it's essential nucleus and the right to health. Social right of the second generation of the fundamental human rights, the right to health is guaranteed by the Federal Constitution, which recognizes its public relevance, that is, the immediate applicability of the norms that assure the solidarity of the public authorities and their responsibility of providing people's health. Furthermore, the court cases, which include the access and supplies of medicines, were also looked into in order to present the actual discussions about the effectiveness of the right to health. Hence, it was also mentioned some of the main objections of the Judiciary performance' ~nd how they can be overcome. Through the study of the minimun threshold and its intrinsic relation to the core of human dignity, it is enhanced the elevance to preserve health and worthy life. Due to the legislation in force, the Judiciary performance the right to health, because this right is an subjective public right and so it may be required judicially. On the contrary, the Judiciary is thought to be under penalty of violating the essence of the Federal Constitution